PENGARUH METODE OUTDOOR LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATERI SPERMATOPHYTA SMA - Ardina, Tiffeni; Ningsih, Kurnia; Ariyati, Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
The research aims to determine the effect of the outdoor learning method on student learning outcomes in the material of Spermatophyta in class X of SMAN 1 Meliau. The study was a quasy-experimental research with a non-equivalent control group design. The sampling technique used saturated sampling with class XB as the experimental class and class XA as the control. The instrument is in the form of a multiple choice test with 20 items. The average student learning outcomes taught using the method of outdoor learning were higher namely 15,85 compared to using conventional method, namely 14,53. The result of U Mann-Whitney test showed that Zcount (-2,26) < -Ztable (-1,96), meaning that there were significant differences between the learning outcomes of students taught using the method of outdoor learning and conventional methods. The effect size value obtained was 0,54 with a category of moderate and gave the effect of 20,54%. Therefore, the method of outdoor learning had an effect on student learning outcomes in the Spermatophyta material in class X SMA Negeri 1 Meliau.Keywords: Effect, Outdoor Learning, Learning Outcome